Time pressure effects on decision-making in intertemporal loss scenarios: an eye-tracking study - Zhou, Yan-Bang; Ruan, Shun-Jie; Zhang, Kun; Bao, Qing; Liu, Hong-Zhi (Frontiers in Psychology, 2024)
This study utilized eye-tracking techniques to investigate decision-making behavior in intertemporal loss scenarios under both time pressure and no time pressure conditions. Results revealed shorter decision-making times and decreased large later (LL) option selection frequency under time pressure. Participants under time pressure exhibited reduced Mean Fixation Duration (MFD) and Search Measure (SM) values, indicating altered information processing. Mediation analyses confirmed that task choice outcomes were influenced by SM and MFD, suggesting a shift towards heuristic decision-making under time pressure.